Systematic identification of microplastics in abyssal and hadal sediments of the Kuril Kamchatka trench. (15th January 2021) - Abel, Serena M.; Primpke, Sebastian; Int-Veen, Ivo; Brandt, Angelika; Gerdts, Gunnar
Abstract: The occurrence of microplastics throughout marine environments worldwide, from pelagic to benthic habitats, has become serious cause for concern. Hadal zones were recently described as the "trash bins of the oceans" and ultimate sink for marine plastic debris. The Kuril region covers a substantial area of the North Pacific Ocean and is characterised by high biological productivity, intense marine traffic through the Kuril straits, and anthropogenic activity. Moreover, strong tidal currents and eddy activity, as well as the influence of Pacific currents, have the potential for long distance transport and retention of microplastics in this area. To verify the hypothesis that the underlying Kuril Kamchatka Trench might accumulate microplastics from the surrounding environments and act as the final sink for high quantities of microplastics, we analysed eight sediment samples collected in the Kuril Kamchatka Trench at a depth range of 5143–8250 m during the Kuril Kamchatka Biodiversity Studies II (KuramBio II) expedition in summer 2016. Microplastics were characterised via Micro Fourier Transform Infrared spectroscopy. All samples were analysed in their entirety to avoid inaccuracies due to extrapolations of microplastic concentrations and polymer diversities, which would otherwise be based on commonly applied representative aliquots. The number of microplastic particles detected ranged from 14 to 209 kg −1 sediment (dry weight) with a total of 15 different plastic polymers detected. Polypropylene accounted for the largest proportion (33.2%), followed by acrylates/polyurethane/varnish (19%) and oxidized polypropylene (17.4%). By comparing extrapolated sample aliquots with in toto results, it was shown that aliquot-based extrapolations lead to severe under- or overestimations of microplastic concentrations, and an underestimation of polymer diversity. Graphical abstract: Image 1 Highlights: Microplastic was found in the abyssal and hadal Kuril Kamchatka trench. The number of microplastic particles detected ranged from 14 to 209 kg −1 sediment. Fifteen different plastic polymers were detected. All microplastic particles were smaller than 375 μm. Extrapolations lead to wrong estimations of microplastic number and diversity. Abstract : Microplastics were detected in the abyssal and hadal zones of the Kuril Kamchatka trench.By comparing extrapolated sample aliquots with in toto results, it was shown that aliquot-based extrapolations lead to severe under- or overestimations of microplastic concentrations and an underestimation of polymer diversity.